Peritoneal dialysis in congestive heart failure - Krishnan, Abirami; Oreopoulos, D.G. (SA Heart Journal, 2017)
Heart failure is a major and growing health problem. There have been major advances in the understanding of pathophysiology of heart failure as a chronic progressive disorder, which has led to newer therapies. Whatever the etiology, many heart failure patients eventually progress to a refractory stage characterized by worsening renal function and resistance to diuretic therapy with attending severe edema. A logical treatment for this “cardiorenal syndrome” is the use of dialysis, which is efficient in treating both the hypervolaemia and azotaemia of refractory heart failure. Though all modalities of dialysis have been tried, peritoneal dialysis (PD) is the simplest choice and offers several advantages. It is an already established long-term home-based therapy and does not require complex machinery or hospital resources. PD is associated with preservation of residual renal function, gentle continuous ultrafiltration, hemodynamic stability, better middle molecule clearance, sodium seiving with maintenance of normonatremia and maybe less inflammation, especially with newer solutions, compared to hemodialysis. In this paper we discuss the potential advantages of PD in the treatment of heart failure, review available literature and lay some foundation for future research.